Dando voltas: efeitos econômicos da implantação de uma nova rodovia: o caso do Rodoanel metropolitano de São Paulo - Maciel, Vladimir Fernandes (2011)
Rodoanel is one of the major public infrastructure investments in the state of São Paulo and one of the largest in Latin America. It is a beltway around the city of São Paulo. The main objective of this Ph.D dissertation is to study the Rodoanel. We estimate the impact of the highway on urban land value near the west section of Rodoanel. The theoretical background used for the analysis is urban economics, especially land use economics.